Design of an Intelligent Disinfection Doormat Based on the Unity of Function and Form - Xu, Ran; Wang, Xu (International Journal of Advanced AI Applications, 2025)
Public places often experience high human traffic, which can easily lead to cross-infection of various viruses. To prevent cross-infection, this study employs the "unity of function and form" design principle to develop an intelligent disinfection doormat suitable for scenarios such as hotels. Based on the requirements of hotel scenarios, the system functions, including intelligent sensing, automatic disinfection, and wireless communication, were first determined. Subsequently, using the STM32F103 microcontroller as the main controller, the hardware system integrating a stress sensor module, an alcohol atomization disinfection module, a Bluetooth communication module, and a display module was designed, culminating in the final three-dimensional structural model. The software workflow was then designed, realizing closed-loop control from human detection to automatic disinfection. Finally, simulations using finite element analysis software verified the doormat's static strength, fatigue performance, and modal characteristics. The results indicate that this design effectively integrates the disinfection function with the doormat form, achieving an efficient, intelligent, and low-maintenance entry disinfection solution with promising application prospects. Attention: I will incorporate the note regarding the Bluetooth module interface for future mobile app monitoring expansion.